TIMP1 promotes microglia M2 polarization through MAPK pathway to ameliorate early brain injury after ischemia - Kangkang Zhao; Zizhao Huang (Hereditas)
Abstract Objective To explore the molecular regulatory mechanisms and biomarkers in regulating early brain injury (EBI) and inflammatory response after ischemic stroke (IS). Methods Gene expression profiles of GSE148350, GSE35338, and GSE58294 were analyzed to screen the core genes involved in EBI after IS. Middle cerebral artery occlusion and reperfusion (MCAO/R) model and oxygen and glucose deprivation and reoxygenation (OGD/R) model were used to construct in vivo and in vitro IS models. In MCAO/R model, the effects of tissue inhibitor of metalloproteinase-1 (TIMP1) were investigated by Zea longa score, brain water content assessment and histological analysis. In OGD/R model, after TIMP1 was overexpressed in BV2 cells, M1 and M2 polarization markers (iNOS and Arg-1) in BV2 cells were detected by Western blot, and the effects of BV2 on the viability and apoptosis of HT22 cells were evaluated by cell counting kit-8 and flow cytometry, respectively. Additionally, the effects of TIMP1 overexpression on MAPK pathway in BV2 cells were also detected by Western blot. Results Two core genes, TIMP1 and vimentin (VIM) were screened from 254 differentially expressed genes in IS. TIMP1 was closely associated with the dysregulation of immune cell infiltration. TIMP1 overexpression significantly mitigated MCAO/R-induced neurological dysfunction, brain edema, neuronal apoptosis and inflammatory response in rats. In vitro, it was revealed that TIMP1 overexpression in BV2 cells increased viability and inhibited apoptosis of HT22 cells. In BV2 cells, TIMP1 overexpression promoted the expression of Agr-1 and inhibited the expression of iNOS. In addition, overexpression of TIMP1 inhibited OGD/R-induced increases in the phosphorylation levels of p38, JNK and ERK proteins in BV2 cells. Conclusion This study identified a post-IS EBI regulator, TIMP1. TIMP1 promotes M2 polarization of microglia and ameliorate neurological injury after IS by inactivating MAPK signaling pathway.